Effectiveness and cost-effectiveness of a loyalty scheme for physical activity behaviour change maintenance: a cluster randomised controlled trial. (November 2018) - Hunter, Ruth F; Murray, Jennifer M; Gough, Aisling; Tang, Jianjun; Patterson, Christopher; French, David P; McIntosh, Emma; Xin, Yiqiao; Kee, Frank; ,
Abstract: Background: The workplace is ideal to encourage habitual physical activity, but little evidence exists on effective behaviour change interventions that lead to sustained behaviour. We aimed to address this gap by evaluating the effectiveness and cost-effectiveness of a loyalty-based intervention on physical activity in public sector employees. Methods: We conducted a cluster randomised wait-list controlled trial in public sector organisations in Northern Ireland, UK. We randomly assigned clusters (1:1) using a computer-generated random sequence. Researchers were masked to allocation, but participants were not. Employees aged 18–65 years with no medical contraindications to physical activity were included. The Physical Activity Loyalty scheme intervention was based on high-street loyalty cards where participants earned points for minutes of activity (monitored via remote sensing) that could be redeemed for rewards (1 min=about £0·03), complemented by evidence-based behaviour change techniques. The primary outcome was objectively measured mean steps per day at 6 months using a validated pedometer (Digi-Walker CW-701, Yamax, Japan) measured during 7 days, assessed with intention-to-treat analysis. Secondary outcomes used for economic analyses, nested within the study, included self-reported health, mental wellbeing, quality of life, work absenteeism and presenteeism, and use of health-care resources. Cost-effectiveness, cost-benefit, and mediation analyses were conducted. This trial is registered with the ISRCTN Registry, number ISRCTN17975376. Findings: Between Sept 1, 2014, and Oct 31, 2015, we recruited and randomly assigned 37 clusters and 853 participants (71% female, mean age 43·6 years [SD 9·6]) to the intervention (19 clusters, 457 participants) or control group (18, 396). Primary outcome data were available for 249 (54·4%) intervention and 236 (59·6%) control participants. Mean steps per day were significantly lower in the intervention group at 6 months (adjusted mean difference −336, 95% CI −612 to −60; p=0·02). The intervention was not cost-effective. There was a 60% probability of the intervention being cost-saving from an employer's perspective arising from reduced absenteeism. Interpretation: Our mixed results pose challenges that are too infrequently exposed in public heath intervention trials. Our incentive level might have been too low to incentivise change, even though it was designed a priori by a contingent valuation survey. Also, major re-structuring of several organisations presented substantial implementation challenges. Funding: National Institute for Health Research Public Health Research (PHR) Programme.